A tridimensional view of the Hispanic Health Paradox: Its relationship with faith, the enclave theory, and familism - Sandoval, Bibiana; Hem-Lee-Forsyth, Shivaughn; Bryant, Hanna (Advances in Social Sciences Research Journal, 2021)
This paper examines the "Hispanic (American) Health Paradox," the juxtaposition of Hispanics’ longer lifespan than the average American amid numerous inequities regarding social determinants of health. Hispanic Americans endure multiple health disparities with a higher incidence and prevalence of chronic conditions. They also experience multiple psychosocial and physical health challenges, including higher rates of food insecurity, poverty, segregation, discrimination, and limited or no access to medical care. Nevertheless, Hispanics enjoy better physical well-being and lower mortality rates when compared to non-Hispanics in the United States (Ruiz et al., 2021). This project aims to analyze the sources of this group’s biosocial advantages and resilience, allowing them to have a longer lifespan amidst their lower health status and increased risk for chronic conditions. It explores the political and social justice implications of these inequities. It also examines the strategies to close the gap on Latinos’ current health care disparities via public policy aspects of federal and state legislature. A narrative review method was utilized to examine the existing literature on this paradoxical effect. Keywords based on Medical Subject Headings (MeSH) used to search resources for relevant studies included: Hispanic health paradox (health paradox, immigrant paradox), ethnic minorities (Latinos, LatinX), health disparities (disproportionate health, health inequities), social justice (healthcare stakeholders, health inequities solutions, inequities recommendations), mental health, physical health, and co-morbidities. A quality assessment of full-text peer-reviewed articles yielded 80 articles to compile this narrative review. The research revealed that, despite glaring disparities in social determinants of health, Hispanic Americans have overall experienced better health outcomes through a culture that emphasizes spirituality, community support, and strong family ties.